Policies & Investments to Support Women in Agriculture: Early Findings from CGD’s COVID-19 Gender and Development Initiative - O’Donnell, Megan (2021)
Megan O’Donnell POLICY SEMINAR Towards Resilient Livelihoods, Food Security, and Nutrition for All: Confronting the Gendered Impacts of COVID-19 Co-Organized by IFPRI, the United States Agency for International Development (USAID) and the World Bank MAR 23, 2021 - 09:30 AM TO 11:00 AM EDT